2021
DOI: 10.1021/acs.inorgchem.1c02633
|View full text |Cite
|
Sign up to set email alerts
|

Function of Doping Ru Element in the Hydrogen Evolution Reaction in Rare-Earth Transition-Metal Intermetallics

Abstract: Transition metal-based intermetallics are promising electrocatalysts for replacing the commercial Pt metal in the hydrogen evolution reaction (HER). In this work, RENi 2 and RERu 0.25 Ni 1.75 (RE = Pr, Tb, and Er) were synthesized and their electrocatalytic HER activities were explored. Among undoped compounds, PrNi 2 exhibits the best performance and requires an overpotential of 55 mV, while partially replacing Ni with Ru element (PrRu 0.25 Ni 1.75 ) can greatly reduce the overpotential to 20 mV at a current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Ruthenium (Ru) is the most inexpensive element among noble metals. , Moreover, Ru possesses a comparable binding for hydrogen (65 kcal mol –1 ) as Pt (62 kcal mol –1 ). Prior investigations suggest that engineering on size, dimension, and composition are effective to optimize the Ru property, for expediting hydrogen generation. Volmer and Heyrovsky processes are the general rate-determining steps for nonacidic hydrogen production, which typically depend on the ability of water dissociation and hydrogen binding, respectively . Henceforth, ration design is desirable to reach high-performance Ru-based HER catalysts.…”
mentioning
confidence: 99%
“…Ruthenium (Ru) is the most inexpensive element among noble metals. , Moreover, Ru possesses a comparable binding for hydrogen (65 kcal mol –1 ) as Pt (62 kcal mol –1 ). Prior investigations suggest that engineering on size, dimension, and composition are effective to optimize the Ru property, for expediting hydrogen generation. Volmer and Heyrovsky processes are the general rate-determining steps for nonacidic hydrogen production, which typically depend on the ability of water dissociation and hydrogen binding, respectively . Henceforth, ration design is desirable to reach high-performance Ru-based HER catalysts.…”
mentioning
confidence: 99%
“…As revealed by the powder X-ray diffraction pattern (XRD) (Figure S2), these compounds belong to the C15 Laves phase (Strukturbericht designation) that adopted a MgCu 2 structural type with cubic space group Fd m . Notice that there is a clear right shift of ScCo 2 among four samples, which implies a small unit cell parameter based on Bragg’s law.…”
Section: Resultsmentioning
confidence: 98%
“…In the initial stage, it was demonstrated that the electrocatalytic HER activities of M Co 2 and M Ru 0.25 Co 1.75 ( M = Sc and Zr) follow the order ScRu 0.25 Co 1.75 > ZrRu 0.25 Co 1.75 > ScCo 2 > ZrCo 2 , which is not surprising based on our previous investigation (Figure S2c). The chronoamperometry (CA) measurement of these samples in 1.0 M KOH “appears” to be stable over a period of 12 h (Figure S2d). Notably, a significant amount of Sc ion (27.97 μmol/L, Table ) was detected in the electrolyte as compared with that of Co ion (3.00 μmol/L) for ScCo 2 after CA measurement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After constructing the models of Ni 3 P and Ni 2 FeP, their total and partial density of states (TDOS and PDOS) were computed with Stuttgart TB-LMTO 4.7 program . The bonding strength and bonding character of the selected atomic interactions (<2.8 Å) were evaluated using the crystal orbital Hamiltonian populations (COHP) method. , The exchange-correlation energy was treated with the local density approximation (LDA) functional and spherical symmetry was assumed for the potential inside each Wigner–Seitz (WS) sphere . WS radii as well as k points were determined by default and k-space integrations were done using the tetrahedron method.…”
Section: Methodsmentioning
confidence: 99%